KONTRIBUSI PURA TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA HINDU - Mardwiatmoko (JAPAM (Jurnal Pendidikan Agama), 2025)
The temple is one of the sacred buildings for Hindus to perform religious activities. Activitiesin the temple are closely related to learning Hindu Religious Education. Until now, there is still nooptimization of the use of temples as an alternative learning resource for students. All aspectscontained in the temple contribute to the achievement of student competence in learning HinduReligious Education. On the material of the form and structure of holy places in Hinduism, allbuildings contained in the tri mandala can function as a source of student learning. In dharma gitaand mantra materials, religious ritual activities in temples can support student learning activitiesthrough listening and practicing activities. In the panca yajñā material, students' practical activitiesthrough their participation in the yajñā ritual in the temple will support the concept of the materialobtained by students in class. In the tri kaya parisudha material, the temple can be a vehicle forstudents in training the application of the tri kaya parisudha concept. The material of prayer facilitiesis carried out through practical learning to make prayer facilities in temples, so that students can betrained in scientific ways of thinking by finding evidence of the truth of the theory of something theyhave learned in class. Teachers should be able to direct, guide, and be an example for students toplay an active role in temple activities.